Measurement of the CP-violating phase phi(s) in the B-s(0) -> J/psi phi(1020) -> mu(+)mu-K+K- channel in proton-proton collisions at root s=13 TeV - (:unkn) unknown (ELSEVIER, 2021)
The CP-violating weak phase ?s and the decay width difference ??s between the light and heavy B0s mass eigenstates are measured with the CMS detector at the LHC in a sample of 48 500 reconstructed B0s? J/I) d (1020) ?11+11? K+K? events. The measurement is based on a data sample corresponding to an integrated luminosity of 96.4 fb?1, collected in proton-proton collisions at ?s = 13 TeV in 2017?2018. To extract the values of ?s and ??s, a time-dependent and flavor-tagged angular analysis of the 11+11?K+K? final state is performed. The analysis employs a dedicated tagging trigger and a novel opposite-side muon flavor tagger based on machine learning techniques. The measurement yields ?s = ?11 ?50 (stat) ? 10 (syst) mrad and ??s = 0.114 ? 0.014 (stat)? 0.007 (syst) ps?1, in agreement with the standard model predictions. When combined with the previous CMS measurement at ?s = 8 TeV, the following values are obtained: ?s = ?21 ? 44 (stat) ? 10 (syst) mrad, ??s = 0.1032 ? 0.0095 (stat) ? 0.0048 (syst) ps?1, a significant improvement over the 8 TeV result. ? 2021 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY license
Keywords: CMS; Physics; Oscillations; B physics; QED RADIATIVE-CORRECTIONS; UNIVERSAL MONTE-CARLO; ANGULAR-DISTRIBUTIONS; PHOTOS